Genome evolution in yeast reveals connections between rare mutations in human cancers - Teng, Xinchen (Microb Cell, 2014)
Cancer cells are riddled with mutations. Less than one percent of these are thought to be mutations that drive cancer phenotypes. However, a recent study conducted on the yeast knockout collections by Teng et al. [Mol. Cell (2013) 52: 485-494] provides hard evidence that single gene deletions/mutations in most non-essential genes can drive the selection for cancer-like mutations.